An attractor of a semiflow generated by a system of phase-field equations without the uniqueness of a solution - Kapustyan, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove the existence of a global compact attractor for a multivalued semiflow generated by a system of phase-field equations with conditions on nonlinearity that do not guarantee the uniqueness of a solution.